2019
DOI: 10.1186/s12917-019-2110-7
|View full text |Cite|
|
Sign up to set email alerts
|

The effectiveness of marine based fatty acid compound (PCSO-524) and firocoxib in the treatment of canine osteoarthritis

Abstract: Background NSAIDs are accepted as the most predictably efficacious medical treatment of the clinical signs of osteoarthritis (OA). The marine-based fatty-acid compound PCSO-524 has been proposed as an adjunctive treatment for canine OA, however benefits of this agent is still controversial. The purpose of this study was to evaluate and compare the effectiveness of PCSO-524 combined with the NSAID firocoxib using force plate gait analysis, orthopedic assessment score (OAS) and canine brief pain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
40
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(49 citation statements)
references
References 20 publications
7
40
0
1
Order By: Relevance
“…The improvement noted in PVF in our study is larger than what has been previously reported. 29 , 32 , 33 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The improvement noted in PVF in our study is larger than what has been previously reported. 29 , 32 , 33 …”
Section: Discussionmentioning
confidence: 99%
“…A positive response was defined as ≥5% increase in mean PVF at a single time point in the treated leg [29][30][31][32][33][34] at months 1, 3, 6, 9, and/or 12 compared with baseline (0 month) for each individual dog evaluated on the force plate.…”
Section: Determination Of Positive Response Based On Pvfmentioning
confidence: 99%
See 1 more Smart Citation
“…CBPI is typically used for the validation of systemic treatment modalities and this study was a one-time local treatment of either one or two elbows. 25,26,27 The use of CBPI to assess the effect of treatment in individual dogs typically requires, and has been used for, a much larger sample size than was used in this smaller study of a novel treatment. 25,26,27 Based on these considerations and the fact that CBPI was developed as a scale analogous to that used in human chronic pain studies to capture an owner's perception of both pain severity and how pain interfered with daily life, 23 we examined the PSS and PIS individually from baseline to each time-point (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…25,26,27 The use of CBPI to assess the effect of treatment in individual dogs typically requires, and has been used for, a much larger sample size than was used in this smaller study of a novel treatment. 25,26,27 Based on these considerations and the fact that CBPI was developed as a scale analogous to that used in human chronic pain studies to capture an owner's perception of both pain severity and how pain interfered with daily life, 23 we examined the PSS and PIS individually from baseline to each time-point (Table 2). PSS signi cantly improved at all time points, except for Day 180, which although not signi cant compared to baseline, was still improved compared with baseline.…”
Section: Discussionmentioning
confidence: 99%